Lead-free tin bar and manufacturing process thereof

By preparing tin-bismuth nanospheres in lead-free tin strips and synthesizing nanocarbides, and using octamine and plant extracts to form hydrophobic films, the uneven dispersion of nanoparticles and susceptible surface corrosion in lead-free tin strips is solved. Problem, high-performance welding materials are achieved.

CN119457577APending Publication Date: 2025-02-18CHANGZHOU FRIEND LEAD-FREE SOLDER METAL LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580574.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the use of lead-free tin strips, the dispersion of nanochromium carbide and nanovanavana carbide is uneven and the surface is easily corroded, which affects its performance.

Method used

Tin-bismuth nanospheres are prepared by using tin chloride and bismuth nitrate as precursors, and nanovanavaporin and nanochromium carbide are synthesized therein to avoid their agglomeration. Meanwhile, a hydrophobic membrane was formed using octamine and plant extracts, and mixed with hydroxypropyl-β-cyclodextrin to form microcapsules to protect the surface of lead-free tin strips.

Benefits of technology

The low melting point, excellent tensile strength and elongation of lead-free tin bars are achieved, while avoiding the agglomeration of nanoparticles and surface corrosion, improving welding quality and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122982810000131
    Figure BDA0005122982810000131
  • Figure BDA0005122982810000141
    Figure BDA0005122982810000141
Patent Text Reader

Abstract

The invention discloses a lead-free tin bar and a manufacturing process thereof, and belongs to the technical field of welding material manufacturing, and the manufacturing process comprises the following steps: mixing and stirring modified tin-bismuth nanospheres, antimony, copper, silver, germanium and tantalum to obtain a mixture; heating the mixture until the mixture is molten, continuously heating, stirring and mixing to obtain molten liquid; and casting the molten liquid into a mold, cooling to room temperature, demolding, dipping into the compound, taking out, and curing to obtain the lead-free tin bar. Gaps in tin-bismuth nanospheres can be filled with nano vanadium carbide and nano chromium carbide synthesized in the tin-bismuth nanosphere system, the compactness of the tin-bismuth nanospheres is improved, the mechanical performance of the lead-free tin bar is improved, the working performance of the lead-free tin bar at the high temperature can be improved through nano vanadium carbide and nano chromium carbide, and the service life of the lead-free tin bar is prolonged. The welding effect of the lead-free tin bar is enhanced; a hydrophobic film formed by octadecylamine can enable the plant extract to be tightly attached to the surface of the lead-free tin bar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding material production, in particular to a lead-free tin bar and a production process thereof. Background Art

[0002] Tin bar is a product of solder. Tin bar can be divided into two types: leaded tin bar and lead-free tin bar. It is mainly used for welding circuit boards. It has applications in the electronics industry, home appliance manufacturing, automobile manufacturing, maintenance industry, etc. It is also used to connect electronic components such as resistors, capacitors, inductors, etc. In leaded tin bar, the lead content is relatively high and exists as a matrix element. For lead-free tin bar, lead as an impurity element exists in lead-free solder and is unavoidable. Therefore, the lead content in lead-free solder is less than 0.1%.

[0003] The ideal substitute for the existing lead-containing tin bars should have the characteristics of low melting point, low resistivity, high joint strength, good wettability and low cost. By adding nano-chromium carbide and nano-vanadium carbide, the grain fineness of the lead-free tin bars can be effectively reduced, and excellent tensile strength and elongation can be maintained. However, nano-chromium carbide and nano-vanadium carbide are unevenly dispersed and easily agglomerated in the lead-free tin bars, which affects the performance of the lead-free tin bars. In addition, the surface of the lead-free tin bars is easily corroded by moisture and oxygen in the air, which affects the performance of the lead-free tin bars. Summary of the invention

[0004] The object of the present invention is to provide a lead-free tin bar and a production process thereof: tin chloride and bismuth nitrate are used as precursors to prepare tin-bismuth nanospheres, which have a low melting point and can complete welding at a low temperature (140-145°C) to avoid thermal damage to the weld; nano-vanadium carbide and nano-chromium carbide synthesized in the tin-bismuth nanospheres can effectively reduce the grain fineness of the lead-free tin bar, enhance the crystal phase structure of tin, and inhibit the generation of tin orthorhombic crystals; and nano-vanadium carbide and nano-chromium carbide are synthesized in the tin-bismuth nanosphere system to avoid the formation of nano-vanadium carbide and nano-chromium carbide. Nano-chromium carbide agglomerates and disperses unevenly in the lead-free tin bar, resulting in its poor ability to refine grains; octadecylamine can form a single-molecule or multi-molecule hydrophobic film on the surface of the lead-free tin bar, which acts as a barrier and prevents water and air from contacting the metal surface, thereby protecting the metal surface from oxygen corrosion. The formed hydrophobic film can tightly fit the plant extract to the surface of the lead-free tin bar; the plant extract and octadecylamine are mixed as the core material, and hydroxypropyl-β-cyclodextrin is used as the wall material to form microcapsules to prevent the plant extract and octadecylamine from being easily decomposed at high temperatures, resulting in antioxidant failure.

[0005] The technical problem to be solved by the present invention is as follows: by adding nano-chromium carbide and nano-vanadium carbide, the grain fineness of the lead-free tin bar can be effectively reduced, and excellent tensile strength and elongation can be maintained; however, the nano-chromium carbide and nano-vanadium carbide are unevenly dispersed and easily agglomerated in the lead-free tin bar, which affects the performance of the lead-free tin bar; and the surface of the lead-free tin bar is easily corroded by moisture and oxygen in the air, which affects the performance of the lead-free tin bar.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A process for producing a lead-free solder bar comprises the following steps:

[0008] S1. Mixing modified tin-bismuth nanospheres, antimony, copper, silver, germanium and tantalum, stirring to obtain a mixture.

[0009] S2. Heat the mixture to 400-430°C to melt for 20-30 minutes, continue to heat to 800-900°C, stir and mix for 20-30 minutes to obtain a molten liquid.

[0010] S3. Cast the molten liquid into a mold, cool to room temperature, demould, immerse in the compound, take out, solidify, and obtain a lead-free solder bar.

[0011] Furthermore, the mass ratio of modified tin-bismuth nanospheres, antimony, copper, silver, germanium, and tantalum is (45-50):(1.1-1.3):(0.7-0.9):(2.2-2.5):(0.03-0.05):(0.05-0.07).

[0012] Furthermore, the curing temperature is 45-55° C., and the curing time is 40-50 min.

[0013] Furthermore, the modified tin-bismuth nanospheres are prepared by mixing the tin-bismuth nanospheres with glucose and dopamine, adding a vanadium source and a chromium source, and then carbonizing at a high temperature.

[0014] Furthermore, the vanadium source is selected from vanadium trioxide.

[0015] Furthermore, the chromium source is selected from chromium nitrate nonahydrate.

[0016] Furthermore, the high temperature carbonization temperature is 1100-1300°C, and the high temperature carbonization time is 1-2h.

[0017] Furthermore, the modified tin-bismuth nanospheres are prepared by the following steps:

[0018] A1. Add tin-bismuth nanospheres to Tris-HCl buffer with a pH of 8.5, stir evenly, add dopamine, ultrasonically treat for 5 minutes, stir at 25°C for 4 hours, add glucose, stir, let stand for 10 minutes, filter, wash with deionized water 3 times, and dry at 70°C for 10 minutes to obtain pretreated tin-bismuth nanospheres.

[0019] A2. Add the pretreated tin-bismuth nanospheres, vanadium source and chromium source to deionized water, stir evenly, place in a 80°C water bath, stir until the water evaporates, dry in a 60°C oven for 10 minutes, take out, grind into powder to obtain a mixture, place the mixture in a tubular furnace, treat at 340°C for 25 minutes, heat to 423°C, keep warm for 25 minutes, continue to heat to 1200°C, carbonize for 1.5 hours, cool to room temperature, and obtain modified tin-bismuth nanospheres.

[0020] Furthermore, during the above-mentioned A1 reaction, the phenolic hydroxyl structure contained in dopamine has good adhesion, and dopamine can self-polymerize in Tris-HCl buffer and can be deposited on the surface of tin-bismuth nanospheres, so that the tin-bismuth nanospheres have high adhesion and can adhere glucose to the surface of tin-bismuth nanospheres. Glucose, as a carbon source, is conducive to the synthesis of nano-chromium carbide and nano-vanadium carbide particles in the tin-bismuth nanosphere system.

[0021] Furthermore, in the above reaction A2, the tin-bismuth nanospheres coated with glucose, the vanadium source, and the chromium source are mixed to form a dispersion, and after water dissolution and evaporation, the vanadium source and the chromium source are tightly combined with the tin-bismuth nanospheres coated with glucose.

[0022] Furthermore, heat treatment is performed at 340°C, so that the glucose molecules in the tin-bismuth nanospheres coated with glucose are thermally decomposed to form carbon elements, and the tin-bismuth nanospheres form a melt, so that the carbon elements are dispersed in the tin-bismuth nanosphere melt; at 423°C, the chromium source chromium nitrate nonahydrate is thermally decomposed to form chromium oxide, and when the temperature is further increased to 1200°C, the vanadium source vanadium trioxide and chromium oxide undergo a carburization reduction reaction with the carbon element in the tin-bismuth nanosphere melt, and the oxygen atoms in the structure of the vanadium source vanadium trioxide and chromium oxide are replaced by carbon atoms, thereby realizing the synthesis of nano-vanadium carbide and nano-chromium carbide in the tin-bismuth nanospheres.

[0023] Furthermore, in step A1, the ratio of tin-bismuth nanospheres, Tris-HCl buffer, dopamine, and glucose is (2-3) g: (45-55) mL: (0.6-1) g: (1-2) g.

[0024] Furthermore, in step A2, the ratio of the amount of pretreated tin-bismuth nanospheres, vanadium source, chromium source, and deionized water is (2-3) g: (1-1.4) g: (1-1.2) g: (45-55) mL.

[0025] Furthermore, the tin-bismuth nanospheres are prepared by ultrasonically treating tin and bismuth nanocrystal precursors and then subjecting them to two-step heating treatment.

[0026] Furthermore, the ultrasonic treatment time is 0.5-1.5h, and the ultrasonic treatment temperature is 0-1°C.

[0027] Furthermore, the heating treatment is performed in two steps: the first step is performed at a temperature of 150-170°C for 25-35 minutes, and the second step is performed at a temperature of 170-190°C for 10-15 minutes.

[0028] Furthermore, the particle size of the tin-bismuth nanospheres is 5-8 μm.

[0029] Furthermore, the tin-bismuth nanospheres are prepared by the following steps:

[0030] The tin and bismuth nanocrystal precursors were ultrasonically treated at 0°C for 1 hour, nitrogen was introduced, and after two-step heating treatment, the first step was 160°C for 30 minutes, and the second step was 180°C for 13 minutes. They were filtered and placed in diethylene glycol for graded sedimentation to remove nanoscale reactants to obtain graded products. The graded products were washed with ethanol and dried in an oven at 50°C for 3 hours to obtain tin-bismuth nanospheres.

[0031] Among them, at 160°C, the tin-bismuth nanocrystal precursor melts, and with the help of mechanical stirring, the nanoseeds collide and agglomerate, gradually gathering into tin-bismuth nanospheres. As the temperature rises to 180°C, the maturation and growth accelerate, the alloy size expands, and tin-bismuth nanospheres with a size of 5-8μm are obtained.

[0032] Furthermore, the usage ratio of tin and bismuth nanocrystal precursors and diethylene glycol is (20-30) g:(50-60) mL.

[0033] Furthermore, the tin and bismuth nanocrystal precursors are specifically prepared by the following steps:

[0034] Tin chloride, bismuth nitrate and polyvinyl pyrrolidone are added to diethylene glycol, stirred evenly, sodium borohydride is added, put into an ice water bath, nitrogen is introduced, stirred at a speed of 180-220rpm for 30-35min, a sodium hydroxide ethanol solution with a concentration of 1.1-1.3mol / L is added to inhibit the self-decomposition of sodium borohydride, stirring is continued for 30-35min, and stored at room temperature to obtain tin and bismuth nanocrystal precursors.

[0035] Among them, tin chloride and bismuth nitrate are used as raw materials, polyvinyl pyrrolidone is used as a dispersant, dissolved in an organic solvent diethylene glycol, and sodium borohydride is used as a reducing agent, so that the tin ions and bismuth ions in the tin chloride and bismuth nitrate are reduced to nano-tin and bismuth, forming tin and bismuth nanocrystal precursors.

[0036] Furthermore, the dosage ratio of tin chloride, bismuth nitrate, polyvinyl pyrrolidine, diethylene glycol, sodium borohydride, and sodium hydroxide ethanol solution is (3-4) g: (6-7) g: (0.6-0.7) g: (60-70) mL: (3-3.6) g: (8-12) mL.

[0037] Furthermore, the composite is prepared by mixing plant extract and octadecylamine as core material, and hydroxypropyl-β-cyclodextrin as wall material to obtain microcapsules, and then mixing the microcapsules, silane coupling agent, polyvinyl alcohol, and deionized water. Specifically, the composite is prepared by the following steps:

[0038] B1. Add hydroxypropyl-β-cyclodextrin to deionized water, stir at 1200 r / min for 20 min at 35°C to obtain solution A; add octadecylamine and plant extract to ethanol, stir at 1200 r / min for 20 min at 35°C to obtain solution B; add 3.5% by mass tween-80 aqueous solution and solution B to solution A, let stand at room temperature for 24 h, filter, wash twice with anhydrous ethanol, wash three times with deionized water, and dry in an oven at 45°C for 20 h to obtain microcapsules.

[0039] B2. Add silane coupling agent to ethanol and deionized water, stir for 20 minutes, add microcapsules, stir and react at 80°C for 2 hours, cool to room temperature, filter, wash with deionized water 3 times, dry in an oven at 80°C for 10 minutes to obtain a solid, mix the solid, polyvinyl alcohol and deionized water to obtain a composite.

[0040] Furthermore, in the above-mentioned B1 reaction process, the plant extract and octadecylamine are mixed as the core material, and hydroxypropyl-β-cyclodextrin is used as the wall material to form microcapsules, so as to prevent the plant extract and octadecylamine from being easily decomposed at high temperature, resulting in antioxidant failure.

[0041] Furthermore, during the above-mentioned B2 reaction process, the silanol groups produced by the hydrolysis of the silane coupling agent can be chemically bonded to the hydroxyl groups on the surface of the nano-capsules, and the amino groups contained in the silane coupling agent are chemically bonded to the hydroxyl groups in the polyvinyl alcohol, so that the nano-capsules are uniformly dispersed in the polyvinyl alcohol. The polyvinyl alcohol, as the base material of the lead-free tin bar anti-corrosion film, has excellent barrier properties to oxygen in the air.

[0042] Furthermore, in step B1, the dosage ratio of hydroxypropyl-β-cyclodextrin, deionized water, octadecylamine, plant extract, ethanol, and tween-80 aqueous solution is (1-3) g:(15-25) mL:(1-1.4) g:(1.6-2) g:(25-35) mL:(1-3) mL.

[0043] Furthermore, in step B2, the ratio of silane coupling agent, ethanol, deionized water and microcapsules is (0.5-1.5) g: (8-12) mL: (60-80) mL: (3-4) g.

[0044] Furthermore, in step B2, the ratio of solid, polyvinyl alcohol and deionized water is (0.2-0.4) g: (2-3) g: (45-55) mL.

[0045] Furthermore, the silane coupling agent is selected from KH550.

[0046] Furthermore, the plant extract is specifically prepared by the following steps:

[0047] The bark was dried outdoors for 72 hours, ground into powder, the powder was added into ethanol, placed in a Soxhlet extraction chamber, flow extracted for 3-5 hours, and the supernatant was taken out to obtain the plant extract.

[0048] Furthermore, the ratio of powder to ethanol is (1-3):(15-25) mL.

[0049] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) In the technical solution of the present invention, tin chloride and bismuth nitrate are used as precursors to prepare tin-bismuth nanospheres, which have a low melting point and can be welded at a low temperature (140-145°C), thereby avoiding thermal damage to the welded object and reducing energy consumption. The tin-bismuth alloy solder has good fluidity after melting and can fill the weld joint to form a uniform weld, thereby improving the welding quality.

[0051] (2) In the technical scheme of the present invention, glucose is adhered to the surface of tin-bismuth nanospheres. Glucose serves as a carbon source, which is beneficial to the synthesis of nano-chromium carbide and nano-vanadium carbide particles in the tin-bismuth nanosphere system; the tin-bismuth nanospheres coated with glucose, the vanadium source, and the chromium source are mixed, and after water dissolution and evaporation, the vanadium source and the chromium source are tightly combined with the tin-bismuth nanospheres coated with glucose; the nano-vanadium carbide and nano-chromium carbide synthesized in the tin-bismuth nanospheres can effectively reduce the grain fineness of the lead-free tin bar, enhance the crystal phase structure of tin, and inhibit the generation of tin orthorhombic crystals, so that the tin bar can maintain excellent tensile strength and elongation in a high temperature environment; and the nano-vanadium carbide and nano-chromium carbide are synthesized in the tin-bismuth nanosphere system to avoid the agglomeration and uneven dispersion of the nano-vanadium carbide and nano-chromium carbide in the lead-free tin bar, resulting in poor grain refinement ability and affecting the mechanical properties of the lead-free tin bar.

[0052] (3) In the technical solution of the present invention, the nano-vanadium carbide and nano-chromium carbide synthesized in the tin-bismuth nanosphere system can be filled into the gaps in the tin-bismuth nanospheres, thereby improving the density of the tin-bismuth nanospheres and the mechanical properties of the lead-free tin bars. Furthermore, the nano-vanadium carbide and nano-chromium carbide can improve the working performance of the lead-free tin bars at high temperatures and enhance the welding effect of the lead-free tin bars. Furthermore, in the process of synthesizing nano-chromium carbide and nano-vanadium carbide, the glucose molecules in the tin-bismuth nanospheres are pyrolyzed to form carbon elements, which have a good binding force on the metal bismuth element in the tin-bismuth nanospheres, thereby preventing the replacement of the bismuth element by elements such as silver, germanium, tantalum, and antimony, thereby affecting the performance of the tin-bismuth nanospheres and causing the use temperature of the lead-free tin bars to rise.

[0053] (4) In the technical solution of the present invention, the plant extract contains a large amount of flavonoids, which are coated on the surface of the lead-free tin bar and can effectively remove free radicals in the air, thereby isolating oxygen and preventing impurities from being generated on the surface of the tin bar, which affects the performance of the lead-free tin bar; octadecylamine can form a single-molecule or multi-molecule hydrophobic film on the surface of the lead-free tin bar, which acts as a barrier and prevents water and air from contacting the metal surface, thereby achieving the purpose of protecting the metal surface from oxygen corrosion, and the formed hydrophobic film can tightly adhere the plant extract to the surface of the lead-free tin bar.

[0054] (5) In the technical scheme of the present invention, plant extracts and octadecylamine are mixed as core materials, and hydroxypropyl-β-cyclodextrin is used as wall materials to form microcapsules, so as to prevent plant extracts and octadecylamine from being easily decomposed at high temperatures, resulting in antioxidant failure. When scratches and other crack defects appear on the surface of the lead-free tin bar, the microcapsule wall cracks to release the plant extracts and octadecylamine, forming a hydrophobic film on the surface of the lead-free tin bar to prevent the occurrence of corrosion reactions; nano-microcapsules, silane coupling agents, and polyvinyl alcohol are mixed so that the nano-microcapsules are evenly dispersed in the polyvinyl alcohol. Polyvinyl alcohol, as the base material of the anti-corrosion film of the lead-free tin bar, has excellent barrier properties to oxygen in the air, and can effectively prevent the lead-free tin bar from contacting with corrosive media such as oxygen in the air, thereby playing an anti-corrosion role. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] The raw materials used in the embodiments of the present invention are as follows:

[0057] Tris-HCl buffer (purity 99%, Wuhan Desheng Biochemical Technology Co., Ltd.); dopamine (Shenzhen Hengfeng Wanda Pharmaceutical Technology Co., Ltd.); glucose (purity 99%, Sinopharm Chemical Reagent Co., Ltd.); vanadium trioxide (purity 99%, Nanchang Cemented Carbide Co., Ltd.); chromium nitrate nonahydrate (purity 99%, Sinopharm Chemical Reagent Co., Ltd.); hydroxypropyl-β-cyclodextrin (analytical grade, Zhejiang Dongjin Biotechnology Co., Ltd.); octadecylamine (purity 98%, Shanghai MacLean Biochemical Co., Ltd.); tween-80 aqueous solution (mass fraction 3.5%, Tianjin Aopu Biochemical Company); KH550 (purity 99%, Zhejiang Woxingman New Material Technology Co., Ltd.); polyvinyl alcohol (alcoholysis degree 98-99%, Shanghai Chuangsai Technology Co., Ltd.); diethylene glycol, sodium hydroxide, sodium borohydride (Shanghai Titan Science Co., Ltd.); tin chloride, bismuth nitrate, polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.).

[0058] Tin and bismuth nanocrystal precursors are specifically prepared by the following steps:

[0059] 3.5 g of tin chloride, 6.6 g of bismuth nitrate, and 0.65 g of polyvinyl pyrrolidone were added to 65 mL of diethylene glycol and stirred evenly. 3.3 g of sodium borohydride was placed in an ice water bath, nitrogen was introduced, and the mixture was stirred at 200 rpm for 33 min. 10 mL of 1.2 mol / L sodium hydroxide ethanol solution was added to inhibit the self-decomposition of sodium borohydride. Stirring was continued for 33 min. The mixture was stored at room temperature to obtain tin and bismuth nanocrystal precursors.

[0060] Example 1

[0061] The modified tin-bismuth nanospheres are specifically prepared by the following steps:

[0062] A1. Ultrasonic treatment of 25 g of tin and bismuth nanocrystal precursors at 0°C for 1 h, nitrogen gas was introduced, and two-step heating treatment was performed, the first step of which was at 160°C for 30 min and the second step of which was at 180°C for 13 min. The product was filtered and placed in 55 mL of diethylene glycol for graded sedimentation to remove the nanoscale reactants to obtain graded products. The graded products were washed with ethanol and dried in an oven at 50°C for 3 h to obtain tin-bismuth nanospheres.

[0063] A2. Add 2.5 g of tin-bismuth nanospheres to 50 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g of dopamine, ultrasonically treat for 5 min, stir at 25 ° C for 4 h, add 1.5 g of glucose, stir, let stand for 10 min, filter, wash with deionized water 3 times, and dry at 70 ° C for 10 min to obtain pretreated tin-bismuth nanospheres.

[0064] A3. Add 2.5 g of pretreated tin-bismuth nanospheres, 1.2 g of vanadium trioxide and 1.1 g of chromium nitrate nonahydrate to 50 mL of deionized water, stir evenly, place in an 80°C water bath, stir until the water evaporates, dry in an oven at 60°C for 10 min, take out, grind into powder to obtain a mixture, place the mixture in a tubular furnace, treat at 340°C for 25 min, heat to 423°C, keep warm for 25 min, continue to heat to 1200°C, carbonize for 1.5 h, cool to room temperature, and obtain modified tin-bismuth nanospheres.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that the tin-bismuth nanospheres are replaced by tin nanospheres, and the remaining steps and raw materials are the same as Example 1.

[0067] A1. Add 2.5 g of tin nanospheres to 50 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g of dopamine, ultrasonically treat for 5 min, stir at 25 ° C for 4 h, add 1.5 g of glucose, stir, let stand for 10 min, filter, wash with deionized water 3 times, and dry at 70 ° C for 10 min to obtain pretreated tin nanospheres.

[0068] A2. Add 2.5 g of pretreated tin nanospheres, 1.2 g of vanadium trioxide and 1.1 g of chromium nitrate nonahydrate to 50 mL of deionized water, stir evenly, place in an 80°C water bath, stir until the water evaporates, dry in an oven at 60°C for 10 min, take out, grind into powder to obtain a mixture, place the mixture in a tubular furnace, treat at 340°C for 25 min, heat to 423°C, keep warm for 25 min, continue to heat to 1200°C, carbonize for 1.5 h, cool to room temperature to obtain modified tin nanospheres.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that glucose, vanadium trioxide and chromium nitrate nonahydrate are not added, and the remaining steps and raw materials are the same as those of Example 1.

[0071] A1. Ultrasonic treatment of 25 g of tin and bismuth nanocrystal precursors at 0°C for 1 h, nitrogen gas was introduced, and two-step heating treatment was performed, the first step of which was at 160°C for 30 min and the second step of which was at 180°C for 13 min. The product was filtered and placed in 55 mL of diethylene glycol for graded sedimentation to remove the nanoscale reactants to obtain graded products. The graded products were washed with ethanol and dried in an oven at 50°C for 3 h to obtain tin-bismuth nanospheres.

[0072] A2. Add 2.5 g of tin-bismuth nanospheres to 50 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g of dopamine, ultrasonically treat for 5 min, stir at 25 °C for 4 h, filter, wash with deionized water 3 times, and dry at 70 °C for 10 min to obtain modified tin-bismuth nanospheres.

[0073] Example 2

[0074] The composite is specifically prepared by the following steps:

[0075] B1. Dry the bark outdoors for 72 hours, grind it into powder, add 2 g of the powder into 20 mL of ethanol, place it in a Soxhlet extraction chamber, perform flow extraction for 4 hours, take out the supernatant, and obtain the plant extract.

[0076] B2. Add 2 g of hydroxypropyl-β-cyclodextrin to 20 mL of deionized water, stir at 1200 r / min for 20 min at 35°C to obtain solution A; add 1.2 g of octadecylamine and 1.8 g of plant extract to 30 mL of ethanol, stir at 1200 r / min for 20 min at 35°C to obtain solution B; add 2 mL of 3.5% tween-80 aqueous solution and solution B to solution A, let stand at room temperature for 24 h, filter, wash twice with anhydrous ethanol, wash three times with deionized water, and dry in an oven at 45°C for 20 h to obtain microcapsules.

[0077] B3. Add 1 g of KH550 to 10 mL of ethanol and 70 mL of deionized water, stir for 20 min, add 3.5 g of microcapsules, stir and react at 80 ° C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80 ° C for 10 min to obtain a solid. Mix 0.3 g of the solid, 2.5 g of polyvinyl alcohol, and 50 mL of deionized water to obtain a composite.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 2 is that no plant extract is added, and the remaining steps and raw materials are the same as Example 2.

[0080] B1. Add 2 g of hydroxypropyl-β-cyclodextrin to 20 mL of deionized water, stir at 1200 r / min for 20 min at 35°C to obtain solution A, add 3 g of octadecylamine to 30 mL of ethanol, stir at 1200 r / min for 20 min at 35°C to obtain solution B; add 2 mL of 3.5% tween-80 aqueous solution and solution B to solution A, let stand at room temperature for 24 h, filter, wash twice with anhydrous ethanol, wash three times with deionized water, and dry in an oven at 45°C for 20 h to obtain microcapsules.

[0081] B2. Add 1 g of KH550 to 10 mL of ethanol and 70 mL of deionized water, stir for 20 min, add 3.5 g of microcapsules, stir and react at 80 ° C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80 ° C for 10 min to obtain a solid. Mix 0.3 g of the solid, 2.5 g of polyvinyl alcohol, and 50 mL of deionized water to obtain a composite.

[0082] Comparative Example 4

[0083] The difference between this comparative example and Example 2 is that the microcapsules are replaced by octadecylamine and plant extracts, and the remaining steps and raw materials are the same as those in Example 2.

[0084] B1. Dry the bark outdoors for 72 hours, grind it into powder, add 2 g of the powder into 20 mL of ethanol, place it in a Soxhlet extraction chamber, perform flow extraction for 4 hours, take out the supernatant, and obtain the plant extract.

[0085] B2. 1.2 g of octadecylamine, 1.8 g of plant extract, 2.5 g of polyvinyl alcohol, and 50 mL of deionized water were mixed to obtain a composite.

[0086] Example 3

[0087] A process for producing a lead-free solder bar comprises the following steps:

[0088] S1. The modified tin-bismuth nanospheres prepared in Example 1, antimony, copper, silver, germanium, and tantalum are mixed and stirred to obtain a mixture, wherein the mass ratio of the modified tin-bismuth nanospheres, antimony, copper, silver, germanium, and tantalum is 45:1.1:0.7:2.2:0.03:0.05.

[0089] S2. The mixture is heated to 400°C to melt for 20 minutes, and then the temperature is further raised to 800°C, and stirred and mixed for 20 minutes to obtain a molten liquid.

[0090] S3. Cast the molten liquid into a mold, cool to room temperature, demould, and then immerse in 50 g of the compound prepared in Example 2, take out, and solidify to obtain a lead-free tin bar.

[0091] Example 4

[0092] A process for producing a lead-free solder bar comprises the following steps:

[0093] S1. The modified tin-bismuth nanospheres prepared in Example 1, antimony, copper, silver, germanium, and tantalum are mixed and stirred to obtain a mixture, wherein the mass ratio of the modified tin-bismuth nanospheres, antimony, copper, silver, germanium, and tantalum is 48:1.2:0.8:2.4:0.04:0.06.

[0094] S2. Heat the mixture to 420°C to melt for 25 minutes, continue to heat to 850°C, stir and mix for 25 minutes to obtain a molten liquid.

[0095] S3. Cast the molten liquid into a mold, cool to room temperature, demould, and then immerse in 50 g of the compound prepared in Example 2, take out, and solidify to obtain a lead-free tin bar.

[0096] Example 5

[0097] A process for producing a lead-free solder bar comprises the following steps:

[0098] S1. The modified tin-bismuth nanospheres prepared in Example 1, antimony, copper, silver, germanium, and tantalum are mixed and stirred to obtain a mixture, wherein the mass ratio of the modified tin-bismuth nanospheres, antimony, copper, silver, germanium, and tantalum is 50:1.3:0.9:2.5:0.05:0.07.

[0099] S2. The mixture is heated to 430°C to melt for 30 minutes, and then the temperature is further raised to 900°C, and stirred and mixed for 30 minutes to obtain a molten liquid.

[0100] S3. Cast the molten liquid into a mold, cool to room temperature, demould, and then immerse in 50 g of the compound prepared in Example 2, take out, and solidify to obtain a lead-free tin bar.

[0101] Comparative Example 5

[0102] The difference between this comparative example and Example 4 is that the modified tin-bismuth nanospheres prepared in Example 1 are replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.

[0103] Comparative Example 6

[0104] The difference between this comparative example and Example 4 is that the modified tin-bismuth nanospheres prepared in Example 1 are replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.

[0105] Comparative Example 7

[0106] The difference between this comparative example and Example 4 is that the composite prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0107] Comparative Example 8

[0108] The difference between this comparative example and Example 4 is that the composite prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.

[0109] The performance of the lead-free tin bars prepared in Examples 3-5 and Comparative Examples 5-8 is now tested;

[0110] Tensile strength: Tested according to the test method in YST1580-2022 "Tensile test method for tin and tin alloys".

[0111] Elongation: Tested according to the test method in SJ / T 11389-2019 "Test Method for Lead-free Solder". The greater the elongation, the better the solderability of the solder bar.

[0112] Peel strength: The peel strength of the copper foil bonded with the lead-free tin bar was tested using a universal testing machine (SHK-A102). The peel speed was fixed at 10 mm / min. The peel strength = F2 / b, where F2: peel strength; b: width of the bonded copper foil sample.

[0113] Anti-corrosion performance: The lead-free tin bar prepared as above was placed in an environment with a humidity of 75%, and the surface of the tin bar was visually inspected to see whether it was smooth and black.

[0114] Temperature detection: Solder the copper foil with the lead-free tin bar prepared above and record the soldering temperature.

[0115] The test results of lead-free solder bars are shown in Table 1 below:

[0116] Table 1

[0117]

[0118]

[0119] It can be seen from the data in Table 1 that in Comparative Example 5, the modified tin nanospheres prepared by replacing the tin-bismuth nanospheres with tin nanospheres are used to prepare lead-free tin bars, and the use temperature thereof increases and the peel strength decreases. This may be because tin chloride and bismuth nitrate are used as precursors to prepare tin-bismuth nanospheres, which have a lower melting point and can be welded at a lower temperature (140-145°C), avoiding thermal damage to the weld, while also reducing energy consumption. The tin-bismuth alloy solder has good fluidity after melting, can fill the weld joint, form a uniform weld, and improve the welding quality. The tin nanospheres lack the bismuth element and cannot achieve this effect. Therefore, the use temperature increases and the peel strength decreases.

[0120] In Comparative Example 6, the modified tin-bismuth nanospheres prepared without adding glucose, vanadium trioxide, and chromium nitrate nonahydrate were used to prepare lead-free tin bars, and their tensile strength and elongation decreased. This may be because the nano-vanadium carbide and nano-chromium carbide synthesized in the tin-bismuth nanospheres can maintain excellent tensile strength and elongation, and the nano-vanadium carbide and nano-chromium carbide are synthesized in the tin-bismuth nanosphere system to avoid agglomeration and uneven dispersion of the nano-vanadium carbide and nano-chromium carbide in the lead-free tin bar. The modified tin-bismuth nanospheres prepared in Comparative Example 6 lack nano-vanadium carbide and nano-chromium carbide, and this effect cannot be achieved, so the tensile strength and elongation decrease.

[0121] In Comparative Example 7, the composite prepared without adding plant extracts was coated on the surface of the lead-free tin bar, and its antioxidant property decreased. This may be because the plant extract contains a large amount of flavonoids, which can effectively remove free radicals in the air, thereby isolating oxygen. Without plant extracts, this effect cannot be achieved, and thus the antioxidant property of the lead-free tin bar decreases.

[0122] In Comparative Example 8, the microcapsules were replaced with a complex prepared by octadecylamine and plant extracts and coated on the surface of the lead-free tin bar. The antioxidant activity was reduced. This may be because the plant extract and octadecylamine were mixed as the core material and hydroxypropyl-β-cyclodextrin was used as the wall material to form microcapsules, which prevented the plant extract and octadecylamine from being easily decomposed at high temperatures, resulting in antioxidant failure.

[0123] The data in Table 1 show that the lead-free tin bars prepared in Examples 3-5 meet the test performance requirements, while the lead-free tin bars prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the lead-free tin bars prepared in the present invention have good solderability, oxidation resistance, and low-temperature performance.

[0124] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0125] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for producing a lead-free solder bar, characterized in that: The following steps are involved: S1. The modified tin-bismuth nanospheres, antimony, copper, silver, germanium and tantalum are mixed and stirred to obtain a mixture; S2. The mixture is heated to 400-430°C for melting for 20-30 minutes, and then the temperature is raised to 800-900°C, and stirred for 20-30 minutes to obtain a molten liquid; S3. The molten liquid is cast into a mold, cooled to room temperature, demolded, immersed in the composite, removed, and cured to obtain a lead-free tin bar; The modified tin-bismuth nanospheres are prepared by mixing tin-bismuth nanospheres with glucose and dopamine, adding vanadium source and chromium source, and carbonizing at high temperature. The tin-bismuth nanospheres are prepared by ultrasonically treating tin and bismuth nanocrystal precursors and then performing two-step heating treatment; The composite is prepared by mixing plant extract and octadecylamine as core material, using hydroxypropyl-β-cyclodextrin as wall material to obtain microcapsules, and then mixing the microcapsules, silane coupling agent, polyvinyl alcohol and deionized water.

2. The process for producing a lead-free solder bar according to claim 1, characterized in that: The tin and bismuth nanocrystal precursors are specifically prepared by the following steps: Tin chloride, bismuth nitrate and polyvinyl pyrrolidone are added to diethylene glycol, stirred evenly, sodium borohydride is added, put into an ice water bath, nitrogen is introduced, stirred at a speed of 180-220rpm for 30-35min, a sodium hydroxide ethanol solution with a concentration of 1.1-1.3mol / L is added to inhibit the self-decomposition of sodium borohydride, stirring is continued for 30-35min, and stored at room temperature to obtain tin and bismuth nanocrystal precursors.

3. The process for producing a lead-free solder bar according to claim 2, characterized in that: The dosage ratio of the tin chloride, bismuth nitrate, polyvinyl pyrrolidine, diethylene glycol, sodium borohydride and sodium hydroxide ethanol solution is (3-4) g: (6-7) g: (0.6-0.7) g: (60-70) mL: (3-3.6) g: (8-12) mL.

4. The process for producing a lead-free solder bar according to claim 1, characterized in that: The ultrasonic treatment time is 0.5-1.5h, and the ultrasonic treatment temperature is 0-1°C; the two-step heating treatment: the first step heating treatment temperature is 150-170°C, the time is 25-35min, and the second step heating treatment temperature is 170-190°C, the time is 10-15min; the particle size of the tin-bismuth nanospheres is 5-8μm.

5. The process for producing a lead-free solder bar according to claim 1, characterized in that: The vanadium source is selected from vanadium trioxide; and the chromium source is selected from chromium nitrate nonahydrate.

6. The process for producing a lead-free solder bar according to claim 1, characterized in that: The plant extract is specifically prepared by the following steps: The bark is dried outdoors, ground into powder, the powder is added into ethanol, placed in a Soxhlet extraction chamber, flow extracted for 3-5 hours, and the supernatant is taken out to obtain the plant extract.

7. The process for producing a lead-free solder bar according to claim 1, characterized in that: The silane coupling agent is selected from KH550.

8. The process for producing a lead-free solder bar according to claim 1, characterized in that: The mass ratio of the modified tin-bismuth nanospheres, antimony, copper, silver, germanium and tantalum is (45-50):(1.1-1.3):(0.7-0.9):(2.2-2.5):(0.03-0.05):(0.05-0.07).

9. The process for producing a lead-free solder bar according to claim 1, characterized in that: The curing temperature is 45-55° C., and the curing time is 40-50 minutes.

10. A lead-free tin bar made by the manufacturing process according to any one of claims 1 to 9.